Kapasitor Shunt Sebagai Korektor Tegangan Bus di Gardu Induk - Muhammad Fahmi Hakim; Slamet Nurhadi; Hanifiyah Darna Fidya Amaral; Diktiaz, Aggahra; Amimah, Anggi; Satria Luthfi Hermawan (Politeknik Negeri Malang, 2023)
Segoromadu Substation has two busbars, namely busbar A and busbar B. Busbar A which has nominal voltage of 150 kV has reached a voltage value of 129.38 kV or experienced voltage drop of 13.75%. The percentage of this voltage drop exceeds a predetermined standard. Therefore, it is necessary to design a shunt capacitor which is then modeled and simulated. Based on calculation and analysis result, capacity of shunt capacitor that should be installed on Bus A is 50 MVAR. After the shunt capacitor was installed, based on simulation, there was an increase of 4.87 kV so the voltage afterward became 139.67 kV or only experienced a voltage drop of 3.19%. So, by installing a shunt capacitor with capacity of 50 MVAR, it can increase busbar voltage of the substation. The shunt capacitor also increases the value of reactive power and current flowing to the busbar.